1 - Métissage in Nineteenth Century Senegal:Hybrid Identity and French Colonialism in a West African Town - Hilary Jones (Afrika Zamani, 2022)
This paper argues that Saint Louis’ peculiarity did not match neither the identity of African societies of the interior nor that of metropolitan France. neither was it identical to notions of sychretism or creolisation. At the contrary, this city gave birth to a cosmopolite society with different national, ethnic linguistic and religious identities comparatively influenced as they were by their relationships with States and societies of the Senegal Valley region, the transatlantic trade. This paper offers a re-reading of accounts by European travellers and officials combined with study of archival records, publications such as the Moniteur du Senegal, private papers and portrait photographs. Based on extensive field work, this paper sheds light on an overlooked aspect of African history and casts new light on modern Atlantic and French colonial history by suggesting that these locations were not solely formed by elite European actors but by local inhabitants of the colonies and remote outposts..